Determinants of social distance in a prison environment - Pass, Michael G. (American journal of criminal justice, 1989)
Social distance is defined as a measured distance of human feelings toward ethnic/racial groups, reflecting race relations and underlying potential for racial tensions. Knowledge of variables' effect on social distance should allow for better understanding those things which may enhance race relations, and decrease racial tensions. The relative importance of a number of variables effecting social distance in a maximum security prison are analyzed here. The data reported in this paper were gathered from a sample of inmates at Eastern New York Correctional Facility and demonstrate that educational level and religious affiliation had significant effects on the overall social distance score; number of times in prison was almost significant; and the variables race, place of residence prior to incarceration, age, and marital status had only minimal effects.